2019
DOI: 10.2739/kurumemedj.ms664006
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Re-Dislocation/Instability After Arthroscopic Bankart Repair: Analysis via Telephone Interviews

Abstract: Current advances in arthroscopic surgery have led to good outcomes for arthroscopic Bankart repair (ABR) for recurrent anterior shoulder dislocation. However, recent studies have reported recurrence rates of 4%-19% after ABR. In our survey conducted from February 2002 to December 2010, the post-ABR re-dislocation rate was 8.8%. In 2011, we began performing the ABR with open Bristow (B) procedure or Remplissage (R) procedure in patients with large glenoid or humeral head bone defects and in patients who play co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Follow-up data show good patient satisfaction after surgical repair. The number of patients who suffer from redislocation after arthroscopic Bankart repair has a high variance in current literature and ranges from 0 to 19% [34,35]. Redislocation rates were low in our collective, comparable with the results of Eren et al, who found a redislocation rate of 7.4% five years following arthroscopic Bankart repair [36].…”
Section: Discussionsupporting
confidence: 85%
“…Follow-up data show good patient satisfaction after surgical repair. The number of patients who suffer from redislocation after arthroscopic Bankart repair has a high variance in current literature and ranges from 0 to 19% [34,35]. Redislocation rates were low in our collective, comparable with the results of Eren et al, who found a redislocation rate of 7.4% five years following arthroscopic Bankart repair [36].…”
Section: Discussionsupporting
confidence: 85%
“…However, this methodology (phone interview) has been previously used to capture postoperative recurrence after shoulder stabilization surgery. 2,17 Nevertheless, we could not evaluate the role of objective or subjective apprehension, which may have influenced the outcomes reported. No functional or radiographic assessments were conducted; thus, no comment on the progression of osteoarthritis or other pathologies was possible.…”
Section: Discussionmentioning
confidence: 99%